Using writing assignments to promote critical thinking, learning and professional identity: The Epidemiology Workplace Writing Repository. (30th January 2018) - August, Ella; Trostle, James A
Abstract: Public health writing assignments can and should be more focused on student problem solving, flexible and critical thinking, and intercultural awareness. Liberal arts college writing assignments increasingly focus on these outcomes, and public health educators can learn from their theories and practices. To construct better writing assignments, teachers of public health would benefit from knowing the types and content of writing that practicing professionals produce outside of graduate schools. We describe a resource to support writing in epidemiology courses, that can also serve as a model for other public health subdisciplines. The Epidemiology Workplace Writing Repository includes job descriptions and workplace writing examples from graduates with epidemiology degrees. The repository materials and teaching guide can support the development of formal and informal writing assignments that adapt for public health graduate schools the best writing practices recommended within liberal arts colleges and universities.